Literatura panegiryczna w historyczno-pedagogicznych badaniach nad szkolną edukacją staropolską - Nowicki, Michał (Biuletyn Historii Wychowania, 2026)
The text analyses the methodological problems faced by researchers of early modern educational practices in the 16th–18th centuries. The key challenge is the use of diverse source materials, such as normative texts, textbooks, student notes, and literary works. The author discusses the usefulness of two research methods – hermeneutics and phenomenology – in the analysis of panegyric content, indicating their role in the reconstruction of the teaching and upbringing process, as well as the experience of the audience. He emphasizes that these texts allow for the capture not only of factual knowledge, but also the spiritual and identity dimension of education in the former Polish-Lithuanian Commonwealth. The article illustrates these methodological assumptions with examples of specific panegyric works created in the school environment.